To Increase the Practice of Hand Washing with the Correct 7-Step Technique for 2 Minutes for Doctors Conducting Vaginal Deliveries from Baseline to 80 % in 4 Weeks - Sarika Gautam; Nisha Malik; Meenakshi Chauhan; Vani Malhotra; Savita Singhal; Roopa Malik; Smiti Nanda (Patient Safety and Quality Improvement Journal, 2022)
Introduction:Hand washing is one of the basic habits to prevent infection from service provider to service seeker. Germs are transmissible from one person to another. Hand washing is an effective measure to prevent infection in a health care setting. Local problem: In the labour room, it was found that doctors who are conducting deliveries are not doing hand washing with the correct steps for 2 minutes as often as they should. Materials and Methods: A quality improvement team was formed. Fishbone analysis was performed to determine handwashing status, and five plan-do-study-act (PDSA) cycles were completed to implement a change intervention, with one change being tested, implemented, studied, and adapted for the next PDSA cycle in each cycle. Interventions: Hand washing resources were made available to students, awareness messages were distributed, and live demonstrations and interactive hand washing instruction were conducted in the labour room. Results: Baseline data showed that 10% of doctors were hand washing; a change intervention was implemented after the first PDSA data rose to 55.5%; further PDSAs 2, 3, and 4 were completed, and handwashing rates improved to 69.1%, 66.1%, 75%, and 80%, respectively. Conclusion:It is very important to identify system dysfunction. Acceptance of the problem is half the solution, and by applying simple methods of quality improvement by an enthusiastic team and continuing motivation to make the desired change happen here, we could change the habits of junior residents.